Formulasi Sediaan Pewarna Pipi dalam Bentuk Padat dengan Menggunakan Ekstrak Buah Buni (Antidesma bunius (L.) Spreng) - Anggitha Ningtias; Zulmai Rani; Ridwanto (Yayasan Literasi Sains Indonesia, 2022)
Buni fruit (Antidesma bunius (L.) Spreng) is a plant that contains anthocyanin pigments that can give a red color. The purpose of this study was to make cheek dye preparations in solid form using buni fruit extract (Antidesma bunius (L.) Spreng) as a dye. The extract was obtained by maceration using 96% ethanol containing 2% citric acid. The cheek coloring formula that was made was using buni fruit dye with a concentration of 10; 12.5; 15 and 17.5%. The tests carried out include: physical quality inspection (homogeneity, polish test, crack test), irritation test, and stability test. Formula with a concentration of 10% produces a pale cream color; preparation with a concentration of 12.5% ​​produces a cream color, a concentration of 15% produces a weak pink color and a concentration of 17.5% produces a dark pink color. The results of the physical quality examination of the preparation showed that the preparation had a homogeneous color, good polish at a concentration of 17.5% because it produced a clear pink color during polishing and did not crack when dropped from a height of 25 cm. Preparations are not irritating. From the observation of the shape, it was found that all the cheek coloring preparations made did not change shape from the initial form of printing for 90 days at room temperature storage. From the results of color observations, all preparations made remained stable during storage at room temperature for 50 days, on day 55 the color of the preparation began to fade, this was due to unstable anthocyanins. The odor of the preparation remained stable in storage for 90 days of observation at room temperature. These results indicate that buni fruit extract can be used as a colorant in cheek coloring preparations.